Sejarah ringkas warisan perkapalan tradisional Melayu - Musa, Hashim; Che Rodi, Rozita; Noor Muhammad, Salmah Jan (Institute of the Malay World and Civilisation, Universiti Kebangsaan Malaysia, 2014)
The Malay civilisation in the past, located in the Malay Archipelago, was a maritime civilisation, being strategically situated midway between the trade sea routes of the western and eastern trading nations. Centres of population and government were found in the major city ports of the region. The variation of the monsoonal winds that blow from the west to the east during summer months and from the east to the west during the winter months, helped to bring ships from different regions. A lull in the wind between the seasons forced the ships to stay put at the harbour which gave traders ample apportunities to trade their goods. Naturally ships plied important roles in such maritime trading atmosphere and the Malays from earlier times had been using various ship classes to fulfill those activities. In this article a description of various ships classes used by the Malay maritime traders will be discussed, namely the big ocean-going ships, the medium size ships that plied the seas and straits within the Malay Archipelago, and the smaller boats that were used along the coasts and rivers.